Quantitative computed tomography detects interstitial lung diseases proven by biopsy - Ariani, Alarico; Imperatori, Andrea; Castiglioni, Massimo; Daffrè, Elisa; Aiello, Marina; Bertorelli, Giuseppina; Chetta, Alfredo; Dominioni, Lorenzo; Rotolo, Nicola (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2018)
Background: The Quantitative chest CT (QCT) is emerging as a promising tool in the assessment of interstitial lung disease (ILD). However, the precise relationship between QCT parameters and the fibrosis detectable in lung tissue, remains to be established. Objectives: The aim of this study was to compare QCT and histopathological features in patients with ILD. Moreover we verified if the QCT assessment is similar in patients with or without a ILD diagnosis proven by a biopsy. Methods: Twenty patients affected by ILD who underwent a chest CT and, later, a lung biopsy, were enrolled. Patients were divided according to the histopathological findings (IPF vs sarcoidosis) in two groups (respectively bIPF and bSarc). Other 20 patients with a radiological diagnosis of IPF were included in a control group (rIPF). All CTs were post-processed with a free software (Horos) in order to obtain an ILD quantitative assessment. Results: There were no differences in terms of gender, smoking habit and spirometric values between patients’ groups. rIPF subjects were older than the other: 70 vs 59 and 47 years (p<0.001). A different distribution of QCT parameters was observed between bIPF and bSarc (p<0.01) while it was comparable within bIPF and rIPF. Conclusions: QCT parameters were similar in subjects affected by the same type of ILD detected with biopsy and with CT alone. These findings make stronger the assumption that QCT can identify the presence of pulmonary fibrosis and, ultimately, that it can represent an useful and effective tool to assess ILD.